Titel prent: Dr. Nolens en de Waarheid : dr. Nolens: "De jood gaat tot het socialisme om het te exploiteeren..." - Hahn, Albert
Titel prent: Dr. Nolens en de Waarheid : dr. Nolens: "De jood gaat tot het socialisme om het te exploiteeren...".